An illustrative comic about the intracellular transit of viruses. - Alemán-Iñiguez, Juan Miguel (Spanish Journal of Medical Education, 2021)
The mechanism of how viruses cross intracellular structures is the model that exemplifies intracellular transit through the endomembrane system, the same that is used in the description of the different intracellular apparatus. The objective was to develop a didactic method that explains a mechanism of molecular biology, such as the comic strip in the transit and intracellular signaling of viruses. A comic-illustrative story was designed where a viral structure is personified by an undercover spy, the fundamental axis of the plot is obtaining the genetic information molecules at the nucleus level, for this it has to go through the various departments of the cell that represent the intracytoplasmic organelles with their functional characteristics, the sequence obeys the communication that the different organelles have from the cell membrane to the nucleus. The development of comics or comics can recreate events and phenomena studied in medical sciences such as biology, having the following results: increase interest, understanding, creativity, the need for knowledge and generation of new ideas in students. The comic is a useful didactic tool in teaching intracellular transit from the graphic narration of a viral model that is transported inside the cell.